Hubungan Kemampuan Fonologi dengan Phonological Awareness Pada Anak Prasekolah Usia 4-6 Tahun di Karanganyar - Nuraini, Fimika Asri; Tirtawati, Dewi; Siswanto, Arif (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
Preschool age children are closely related to language and speech development. Mastery of speech clarity and awareness of letter sounds is one aspect of children's readiness to master letters in each vocabulary. Phonological skills affect the achievement of children's phonological awareness, without good phonological skills and phonological awareness skills, children can experience problems in their reading skills. Learning about the structure of language sounds can build phonological awareness skills necessary for reading success during the preschool years. Children who have speech sound production problems in phonology rules, tend to have difficulties in phonology awareness and reading. This study aims to determine whether there is a relationship between phonological ability and phonological awareness in preschool children in Karanganyar. The method used in this study is a quantitative method with correlational research and cross sectional. The sample was taken from 41 respondents with phonological problems with purposive sampling. Data was collected using test instrument. The results of the analysis using the Spearman Rank correlation test obtained a (p) value of 0.004 (p <0.05) which means that there is a relationship between phonological ability and phonological awareness ability in preschool children aged 4-6 years in Karanganyar. The magnitude of the correlation is indicated by the correlation coefficient (r) value of 0.444, meaning that it has a moderate positive correlation. This relationship can be concluded that phonological ability affects the achievement of phonological awareness ability in reading readiness of preschool children.